Toward the IR Detection of Carbonic Acid: Absorption and Emission Spectra - Ryan C. Fortenberry; Vincent J. Esposito (The Astrophysical Journal, 2024)
With the recent radioastronomical detection of cis-trans- carbonic acid (H _2 CO _3 ) in a molecular cloud toward the Galactic center, the more stable but currently unobserved cis-cis conformer is shown here to have strong IR features. While the higher-energy cis-trans- carbonic acid was detected at millimeter and centimeter wavelengths, owing to its larger dipole moment, the vibrational structure of cis-cis- carbonic acid is more amenable to its observation at micron wavelengths. Even so, both conformers have relatively large IR intensities, and some of these fall in regions not dominated by polycyclic aromatic hydrocarbons. Water features may inhibit observation near the 2.75 μ m hydride stretches, but other vibrational fundamentals and even overtones in the 5.5–6.0 μ m range may be discernible with JWST data. This work has employed high-level, accurately benchmarked quantum chemical anharmonic procedures to compute exceptionally accurate rotational spectroscopic data compared to experiment. Such performance implies that the IR absorption and even cascade emission spectral features computed in this work should be accurate and will provide the needed reference for observation of either carbonic acid conformer in various astronomical environments.